Social Reactions to Sexual Assault Disclosure, Coping, Perceived Control and PTSD Symptoms in Sexual Assault Victims - Ullman, Sarah E. (2014)
The social reactions that sexual assault victims receive when they disclose their assault have been found to relate to posttraumatic stress disorder (PTSD) symptoms. Using path analysis and a large sample of sexual assault survivors (N = 1863), we tested whether perceived control, maladaptive coping, and social and individual adaptive coping strategies mediated the relationships between social reactions to disclosure and PTSD symptoms. We found that positive social reactions to assault disclosure predicted greater perceived control over recovery, which in turn was related to less PTSD symptoms. Positive social reactions to assault disclosure were also associated with more adaptive social and individual coping; however, only adaptive social coping predicted PTSD symptoms. Negative social reactions to assault disclosure were related to greater PTSD symptoms both directly and indirectly through maladaptive coping and marginally through lower perceived control over recovery.